Mellom åpne og målstyrte prosesser i samskapingsprosessen av et psykodrama: en prosessanalytisk tilnærming med hovedfokus på noen dramaturgiske beslutninger - Skar, Siri M. (Peripeti, 2022)
The co-creation process of a psychodrama is examined through a process analysis (Krøgholt, 2002), in which some dramaturgical decisions in this process are identified. The sequence in which a disagreement arises between two psychodrama leaders about the last scene of the psychodrama is problematised through a perspective analysis level based on Szatkowski’s (2019) theory of poetic hierarchy and a potential paradox of participation in psychodrama is pointed out.